Contribution of Skill Test in Employment among Short Term Vocational Training Graduates - Pandit, Bhanu; Pasa, Rajan Binayek (Nepalese Journal of Development and Rural Studies, 2020)
This study analyzed contribution of vocational skills tests to the employment of trained graduates in different stages. In doing so, specialized survey was conducted with 305 graduates who received the skill training from private training institutes and attended the level-one skill test of NSTB. The results showed that skill testing system contributed to the employment of graduates specifically by accessing employment opportunities (pre-employment stage), increasing work performance (during- employment stage) and further job prosperity (post-employment). The segregation of the overall results showed that most of the graduates perceived that skill test contributed to all the employment stages.Men and women are equally benefitted with the skill tests to their employment. Similarly, youths from all age groups, all ethnic groups and all educational backgrounds were benefited in a similar manner from the skills test. However, it mattered whether a graduate was married or not, and which geographical area the graduate came from. As an implication, considering the contribution of the skill tests, the investment in skill tests in each of the vocational training is considered valuable and useful not only for the domestic workers including the migrants and returnees. Similarly, skills gained in the form of prior learning through informal and non-formal means can be tested, certified and recognized. Moreover, why the contribution of the skill tests varied according to the graduates’ marital status and geographic origin, a finding of the study, remains an area for further research.